2014
DOI: 10.7235/hort.2014.13030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Several Paper Bags on Fruit Skin Coloration of Red Skin European Pear ‘Kalle’

Abstract: This study was conducted to elucidate the relationship between light and coloring and to obtain basic results for promoting redness expression in 'Kalle' (Pyrus communis L.) pear skin. It was investigated in location of anthocyanin layer by microscopic observation and differences in skin color expression of 'Kalle' bagged with paper bag which has different light transmittance rate and inside temperature. However, there was no anthocyanin layer in the brown skin and golden yellow color, anthocyanin layer was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, the same authors indicated PyMYB10 as the key regulator of anthocyanin biosynthesis in response to light [ 88 ]. Kim et al [ 89 ] confirmed that in P. communis (cultivar “Kalle”), the anthocyanin contents in unbagged fruits remain higher than in bagged fruit. Qian et al [ 90 ] employed bagging to study the light control of anthocyanin biosynthesis in pear fruit, demonstrating that miR156 was expressed in peels, increased after removing the bags, targeted four SPL genes and, additionally, PpSPL10 and PpSPL13 interact with PpMYB10.…”
Section: Bagging and The Color Of Fruitsmentioning
confidence: 99%
“…Additionally, the same authors indicated PyMYB10 as the key regulator of anthocyanin biosynthesis in response to light [ 88 ]. Kim et al [ 89 ] confirmed that in P. communis (cultivar “Kalle”), the anthocyanin contents in unbagged fruits remain higher than in bagged fruit. Qian et al [ 90 ] employed bagging to study the light control of anthocyanin biosynthesis in pear fruit, demonstrating that miR156 was expressed in peels, increased after removing the bags, targeted four SPL genes and, additionally, PpSPL10 and PpSPL13 interact with PpMYB10.…”
Section: Bagging and The Color Of Fruitsmentioning
confidence: 99%
“…Fruit bags that differ in light transmittance differentially affect fruit color. Fruit enclosed in a white paper bag develops red coloration of greater intensity than fruit enclosed in a double black paper bag or double yellow paper bag [24]. Pre-harvest bag picking is mostly used in production to promote fruit coloring, so as to achieve good-quality attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The Nicalon SiC fiber's applicable temperature is now at 1200℃ [4], fiber at higher temperatures is difficult to use mainly for second reasons, inside of fiber, the oxygen with Si and C form the amorphous Si-C-O structure, the fiber escape low molecule weight matter under the high temperature, the pyrolytic reaction destroyed the chain structure of the fiber and cause fiber apparent weightlessness, the surface and internal of fiber produce porous structure defects. The thermal decomposition reaction of SiC fiber are expressed as [5]…”
Section: Introductionmentioning
confidence: 99%